PENINGKATAN NILAI TAMBAH CURUG BANDUNG, DESA SUMINGKIR, KECAMATAN KUTASARI, KABUPATEN PURBALINGGA SEBAGAI DESTINASI GEOWISATA BARU - FX Anjar Tri Laksono; Purwanto Bekti Santoso; Indra Permanajati (Dinamika Journal : Pengabdian Masyarakat, 2020)
Sumingkir Village, Kutasari District, Purbalingga Regency has attractive natural tourism potential. Curug Bandung is a natural phenomenon that can develop to be a new geo-tourism destination for local tourists. Before the revitalization, the number of tourists that visited Curug Bandung was very slight. This happens because it has not been well ordered. Therefore, this activity aims to assist village communities in the revitalization of Curug Bandung to be a tourist attraction that is full of visitors. In this activity, the area around Curug Bandung was cleaned of rubbish and provided a special place for fishing grounds. The dam was carried out to hold the water flow from the waterfall to the river so that the depth of the bathing pool under the waterfall increased. Supporting facilities such as coffee shops and food courts are also built as a place to rest and relax the visitors after soaking in a waterfall. Every visitor who wants to visit a tourist attraction pays an entrance ticket for Rp. 20,000 each person. The income is used for the Curug Bandung conservation site. Tourism conscious community was formed as the party responsible for the management of Bandung Waterfall. The conclusion of this study is the revitalization of Curug Bandung has succeeded in increasing the number of local tourist visits and become a new income for the Sumingkir Village.